Atravessando o Mar Egeu: atuação do profissional de Psicologia em organização não governamental para refugiados - Silvestri, Patricia Rebello (2020)
The migration phenomenon has been addressed by several authors and remains a current topic. Most countries have been dealing with a large flow of immigration or emigration. Psychology literature emphasizes the psychological processes that occur with migrants in the society that welcomes them. According to a report by the United Nations High Commissioner for Refugees (UNHCR, 2019), there are more than 70.8 million refugees. The objective of the present research was to characterize the performance of the psychology professional from his own perspective and from the perspective of the professionals of the interdisciplinary teams in an NGO serving refugees, in light of possible contributions from Environmental Psychology. We proposed qualitative research, case study, and as data sources: NGO documents and semi-structured interviews with a Psychology professional and five other members of the interdisciplinary care team. The results were organized into two major themes: motivation to choose the job at the NGO in focus and the role of the Psychology professional, addressing: characteristics of the service, participation in an interdisciplinary team, difficulties encountered, convergences between the perceptions of the psychologist and those of others team members about their work, inclusion in the NGO, descriptions of a typical day and an atypical one. We analyze possible contributions of Environmental Psychology, from concepts such as appropriation of space and attachment to the place, in the psychologist's work with refugees. We present reflections on the performance of the professional in Psychology in the third sector, considering references of Environmental Psychology and Clinical Psychology, in person-environment interactions in displacements due to environmental catastrophes and forced immigration. We propose this possible confluence field in the care of refugees, as an invitation to psychologists for practices sensitive to the context of refugees, in the recognition of the multiplicity of psychological practices and in the political implications of the different types of psychological activity. This work was supported by the Coordination for the Improvement of Higher Education Personnel - Brazil (CAPES) and by the National Council for Scientific and Technological Development (CNPq)